Effect of Immunization of The Pili Protein 65.5 kDa Klebsiella pneumoniae on IFN-Î³ Levels of Spleen BALB/c Mice - Sa'adah, Ajeng Samrotu; Mufida, Diana Chusna; Dini Agustina; Pulong Wijang Pralampita (Institute of Topical Disease Universitas Airlangga, 2024)
Klebsiella pneumoniae is a Gram-negative bacterium that poses a threat to the global community. Currently, no vaccine for K. pneumoniae is licensed by the Food and Drug Administration (FDA). The delay in the manufacture of the K. pneumoniae vaccine was because many vaccine candidates failed at the clinical trial stage due to adverse cross-reactions. Pili can be used as a choice as a vaccine candidate. Pili K. pneumoniae is an immunogenic substance that triggers an immune response, one of which is the cytokine IFN-Î³. Splenic splenocytes are the main source of IFN-Î³-producing cells. The aim of this study is to determine the effect of immunization pili protein 65.5 kDa K. pneumoniae on IFN-Î³ levels from spleen BALB/c mice. There were 3 groups, K1 as control given PBS, K2 given pili protein 65.5 kDa + adjuvant, and K3 given adjuvant. IFN-Î³ was then measured by the ELISA method and analyzed by the ANOVA test. The results of measuring IFN-Î³ levels using One-way ANOVA showed that the total for all groups was 243.50 ± 43.7 with p < 0.05, the Post Hoc LSD test was continued. The Post Hoc test showed significant differences between K1 control and K2 groups, and between K1 and K3 groups, but not between K2 and K3 groups. It can be concluded that immunization with 65.5 kDa of pili protein does not affect the increase in IFN-Î³ levels in the spleen of BALB/c mice.